Campylobacter jejuni biofilms contain extracellular DNA and are sensitive to DNase I treatment - Brown, Helen L.; Hanman, Kate; Reuter, Mark; Betts, Roy P.; Van Vliet, Arnoud H. (Frontiers in Microbiology, 2015)
Biofilms make an important contribution to survival and transmission of bacterial pathogens in the food chain. The human pathogen Campylobacter jejuni is known to form biofilms in vitro in food chain-relevant conditions, but the exact roles and composition of the extracellular matrix are still not clear. Extracellular DNA has been found in many bacterial biofilms and can be a major component of the extracellular matrix. Here we show that extracellular DNA is also an important component of the C. jejuni biofilm when attached to stainless steel surfaces, in aerobic conditions and on conditioned surfaces. Degradation of extracellular DNA by exogenous addition of DNase I led to rapid biofilm removal, without loss of C. jejuni viability. Following treatment of a surface with DNase I, C. jejuni was unable to re-establish a biofilm population within 48 hr. Similar results were obtained by digesting extracellular DNA with restriction enzymes, suggesting the need for high molecular weight DNA. Addition of C. jejuni genomic DNA containing an antibiotic resistance marker resulted in transfer of the antibiotic resistance marker to susceptible cells in the biofilm, presumably by natural transformation. Taken together, this suggest that eDNA is not only an important component of C. jejuni biofilms and subsequent food chain survival of C. jejuni, but may also contribute to the spread of antimicrobial resistance in C. jejuni. The degradation of extracellular DNA with enzymes such as DNase I is a rapid method to remove C. jejuni biofilms, and is likely to potentiate the activity of antimicrobial treatments and thus synergistically aid disinfection treatments.